Polyproline fold-In imparting kinetic stability to an alkaline serine endopeptidase - Rohamare, Sonali B.; Dixit, Vaishali; Nareddy, Pavan Kumar; Sivaramakrishna, D.; Swamy, Musti J.; Gaikwad, Sushama M. (Biochimica Et Biophysica Acta-Proteins and Proteomics, 2013)
Polyproline II (PPII) fold, an unusual structural element was detected in the serine protease from Nocardiopsis sp. NCIM 5124 (NprotI) based on far UV circular dichroism spectrum, structural transitions of the enzyme in presence of GdnHCl and a distinct isodichroic point in chemical and thermal denaturation. The functional activity and conformational transitions of the enzyme were studied under various denaturing conditions. Enzymatic activity of NprotI was stable in the vicinity of GdnHCl upto 6.0 M concentration, organic solvents viz, methanol, ethanol, propanol (all 90% v/v), acetonitrile (75% v/v) and proteases such as trypsin, chymottypsin and proteinase K (NprotI:protease 10:1). NprotI seems to be a kinetically stable protease with a high energy barrier between folded and unfolded states. Also, an enhancement in the activity of the enzyme was observed in 1 M GdnHCl upto 8 h, in organic solvents (75% v/v) for 72 h and in presence of proteolytic enzymes. The polyproline fold remained unaltered or became more prominent under the above mentioned conditions. However, it diminished gradually during thermal denaturation above 60 degrees C. Thermal transition studies by differential scanning calorimetry (DSC) showed scan rate dependence as well as irreversibility of denaturation, the properties characteristic of kinetically stable proteins. This is the first report of PPII helix being the global conformation of a non structural protein, an alkaline serine protease, from a microbial source, imparting kinetic stability to the protein. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Conformation; differential scanning calorimetry; Kinetic stability; Nocardiopsis sp.; Polyproline fold; Serine protease

Subtilase from Beauveria sp.: conformational and functional investigation of unusual stability - Dalal, Sayli A.; More, Snehal V.; Shankar, Shiv; Laxman, Ryali Seeta; Gaikwad, Sushama M. (European Biophysics Journal With Biophysics Letters, 2014)
Retention of total activity of the subtilisin-like serine protease from Beauveria sp. MTCC 5184 (Bprot) in the vicinity of (1) 3 M GdnHCl for 12 h, (2) 50 % methanol and dimethyl sulfoxide each for 24 h, and (3) proteolytic enzymes (trypsin, chymotrypsin, and proteinase K) for 48 h led to expect the enzyme to be a kinetically stable protein. Also, the structure of the protein was stable at pH 2.0. Biophysical characterization and conformational transitions were monitored using steady-state and time-resolved fluorescence, FTIR, and CD spectroscopy. Single tryptophan in the protein exists as two conformers, in hydrophobic and polar environment. The secondary structure of Bprot was stable in 3 M GdnHCl as seen in far-UV CD spectra. The active fraction of Bprot obtained from size-exclusion chromatography in the presence of GdnHCl (1.0-3.0 M) eluted at reduced retention time. The peak area of inactive or denatured protein with the same retention time as that of native protein increased with increasing concentration of denaturant (1.0-4.0 M GdnHCl). However, the kinetics of GdnHCl-induced unfolding as studied from intrinsic fluorescence revealed k (unf) of native protein to be 5.407 x 10(-5) s(-1) and a half-life of 3.56 h. The enzyme is thermodynamically stable in spite of being resistant to the denaturant, which could be due to the effect of GdnHCl imparting rigidity to the active fraction and simultaneously unfolding the partially unfolded protein that exists in equilibrium with the folded active protein. Thermal and pH denaturation of Bprot exhibited interesting structural transitions.
Keywords: Beauveria; Chemical denaturation; Conformational transitions; Serine protease; Subtilase; Thermal denaturation; Thermodynamic stability

Tryptophan environment and functional characterization of a kinetically stable serine protease containing a polyproline II fold - Rohamare, Sonali B.; Gaikwad, Sushama M. (Journal of Fluorescence, 2014)
The single tryptophan residue from Nocardiopsis sp. serine protease (NprotI) was studied for its microenvironment using steady state and time-resolved fluorescence. The emission maximum was observed at 353 nm with excitation at 295 nm indicating tryptophan to be solvent exposed. Upon denaturation with 6 M guanidinum thiocyanate (GuSCN) the emission maxima was shifted to 360 nm. Solute quenching studies were performed with neutral (acrylamide) and ionic (I- and Cs+) quenchers to probe the exposure and accessibility of tryptophan residue of the protein. Maximum quenching was observed with acrylamide. In the native state, quenching was not observed with Cs+ indicating presence of only positively charged environment surrounding tryptophan. However; in denatured protein, quenching was observed with Cs+, indicating charge reorientation after denaturation. No quenching was observed with Cs+ even at pH 1.0 or 10.0; while at acidic pH, a higher rate of quenching was observed with KI. This indicated presence of more positive charge surrounding tryptophan at acidic pH. In time resolved fluorescence measurements, the fluorescence decay curves could be best fitted to monoexponential pattern with lifetimes of 5.13 ns for NprotI indicating one conformer of the trp. Chemical modification studies with phenyl glyoxal suggested presence of Arg near the active site of the enzyme. No inhibition was seen with soyabean trypsin and limabean inhibitors, while, CanPI uncompetitively inhibited NprotI. Various salts from Hofmeister series were shown to decrease the activity and PPII content of NprotI.
Keywords: Fluorescence quenching; Hofmeister series; Nocardiopsis; Serine protease; Tryptophan

Functional stability and structural transitions of kallikrein: spectroscopic and molecular dynamics studies - Dalal, Sayli; Mhashal, Anil; Kadoo, Narendra; Gaikwad, Sushama M. (Journal of Biomolecular Structure & Dynamics, 2017)
Kallikrein, a physiologically vital serine protease, was investigated for its functional and conformational transitions during chemical (organic solvents, Gdn-HCl), thermal, and pH induced denaturation using biochemical and biophysical techniques and molecular dynamics (MD) simulations approach. The enzyme was exceptionally stable in isopropanol and ethanol showing 110% and 75% activity, respectively, after 96h, showed moderate tolerance in acetonitrile (45% activity after 72h) and much lower stability in methanol (40% activity after 24h) (all the solvents [90% v/v]). Far UV CD and fluorescence spectra indicated apparent reduction in compactness of KLKp structure in isopropanol system. MD simulation studies of the enzyme in isopropanol revealed (1) minimal deviation of the structure from native state (2) marginal increase in radius of gyration and solvent accessible surface area (SASA) of the protein and the active site, and (3) loss of density barrier at the active site possibly leading to increased accessibility of substrate to catalytic triad as compared to methanol and acetonitrile. Although kallikrein was structurally stable up to 90 degrees C as indicated by secondary structure monitoring, it was functionally stable only up to 45 degrees C, implicating thermolabile active site geometry. In GdnHCl [1.0M], 75% of the activity of KLKp was retained after incubation for 4h, indicating its denaturant tolerance. A molten globule-like structure of KLKp formed at pH 1.0 was more thermostable and exhibited interesting structural transitions in organic solvents. The above results provide deeper understanding of functional and structural stability of the serine proteases at molecular level.
Keywords: isopropanol tolerance; Kallikrein; MD Simulation; Molten globule; Serine protease; Thermostability